Time to Surgery and Survival in Head and Neck Cancer - Rygalski, Chandler J. (Ann Surg Oncol, 2020)
BACKGROUND: The COVID-19 pandemic has required triage and delays in surgical care throughout the world. The impact of these surgical delays on survival for patients with head and neck squamous cell carcinoma (HNSCC) remains unknown. METHODS: A retrospective cohort study of 37 730 patients in the National Cancer Database with HNSCC who underwent primary surgical management from 2004 to 2016 was performed. Uni- and multivariate analyses were used to identify predictors of overall survival. Bootstrapping methods were used to identify optimal time-to-surgery (TTS) thresholds at which overall survival differences were greatest. Cox proportional hazard models with or without restricted cubic splines were used to determine the association between TTS and survival. RESULTS: The study identified TTS as an independent predictor of overall survival (OS). Bootstrapping the data to dichotomize the cohort identified the largest rise in hazard ratio (HR) at day 67, which was used as the optimal TTS cut-point in survival analysis. The patients who underwent surgical treatment longer than 67 days after diagnosis had a significantly increased risk of death (HR, 1.189; 95% confidence interval [CI], 1.122–1.261; P < 0.0001). For every 30-day delay in TTS, the hazard of death increased by 4.6%. Subsite analysis showed that the oropharynx subsite was most affected by surgical delays, followed by the oral cavity. CONCLUSIONS: Increasing TTS is an independent predictor of survival for patients with HNSCC and should be performed within 67 days after diagnosis to achieve optimal survival outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1245/s10434-020-09326-4) contains supplementary material, which is available to authorized users.